Feasibility and Safety of a Powered Exoskeleton for Balance Training for People Living with Multiple Sclerosis: A Single-Group Preliminary Study (Rapper III) - Mohamed Sakel; Karen Saunders; Philip Hodgson; David Stephensen; Chetan P. Phadke; Paul A. Bassett; David Wilkinson (Medical Journals Sweden, 2022)
Objective: To evaluate the feasibility, usability, safety, and potential health benefits of using an exoskeleton device for rehabilitation of people living with multiple sclerosis. Design: Single-group preliminary study. Subjects: Eleven adults living with multiple sclerosis, with Expanded Disability Status Scores that ranged from 6 to 7.5 (mean age (standard deviation; SD) 54.2 (11.8) years), were recruited. Methods: Individual participants undertook a balance rehabilitation exercise programme using the Rex Rehab robotic exoskeleton device. Each participant undertook 4 × 45-60 min supervised, balance exercise sessions. Primary outcomes were: (i) the number of participants who completed the trial protocol safely, and (ii) the number and nature of adverse events reported. Secondary outcomes were: mobility; balance; spasticity; sleep; functional independence; quality of life; and device satisfaction. Results: Ten out of 11 participants completed the trial protocol safely. Four adverse events were recorded (1 serious), all of which were deemed unrelated to the trial. Secondary outcomes showed allied improvements in balance, joint mobility, spasticity and quality of life. All participants found the device acceptable to use. Conclusion: These results suggest that it is feasible and safe to use the Rex Rehab exoskeleton device to assist with balance rehabilitation for people living with multiple sclerosis. LAY ABSTRACT Multiple sclerosis (MS) is a chronic neurological disease that can lead to symptoms, including muscle weakness and balance issues. The incidence of falls in people living with MS (PwMS) is 3 times higher than that in older people. To try to reduce this vulnerability to falls, this study aimed to evaluate the feasibility, safety, and potential health benefits of using an exoskeleton device for a balance exercise programme. Eleven PwMS undertook 4×45-60 min supervised, balance exercise sessions using the exoskeleton device. Feasibility and safety were assessed by identifying the number of participants who completed the trial safely; consideration of any issues experienced during the trial and how these were resolved. Ten participants completed the trial (1 withdrew due to their MS) and only 4 issues were reported, all of which were unrelated to the trial. Some participants also experienced improvements in balance, mobility, and quality of life.